PENGARUH PROFITABILITAS, SOLVABILITAS DAN LIKUIDITAS TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR KESEHATAN - Talitha Aprilla Andreani, (2023)
The existence of the Covid-19 pandemic has made Indonesian people aware of the importance of health. The impact of Covid-19 has an impact on the health sector, of course. This research is quantitative research that aims to determine the effect of profitability, solvency, and liquidity on stock prices in health sector companies listed on the Indonesia Stock Exchange. The sample used in this study amounted to 35 sample data. Samples were taken using purposive sampling technique. The tests used are the t test and the coefficient of determination test using the E-Views 12 program. The test results are (1) profitability has a positive and significant effect on stock prices, (2) solvency has a negative and significant effect on stock prices, (3) and liquidity has no effect on share prices of health sector companies listed on the Indonesia Stock Exchange in the 2017 - 2021 period.